Active Deep Learner Experience as an Instructional Strategy in Qur’anic Learning: Links to Engagement, Comprehension, and Retention - Srigunana Sembiring; Muhammad Riduan Harahap; Rukmana Prasetyo (Ambarsa : Jurnal Pendidikan Islam, 2026)
This study aims to explore the implementation of the Active Deep Learner Experience (ADLX) method in Qur'anic learning, and to identify the supporting and hindering factors of its application. The research employs a qualitative approach with a descriptive design. Data was collected through in-depth interviews, participatory observations, and documentation involving the school principal, vice principal, Qur'an coordinator, Qur'an teachers, and 11th-grade students. The findings indicate that the application of the ADLX method in Qur'anic learning has fostered a more active, innovative, and enjoyable learning environment. The learning process is no longer teacher-centre but encourages the active involvement of students in understanding the meanings of Qur'anic verses. This is achieved through stages that include an opening, the core activities (which involve the practice of good manners, talaqqi memorization, and memorization reviews), and a closing with reflection. The supporting factors include adequate facilities and infrastructure, supporting extracurricular programs such as mukhayyam Al-Qur'an and MHQ, ongoing teacher training, and effective coordination among stakeholders. However, there are also hindering factors, including the lack of teacher understanding of the new method, the need for adaptation to the Merdeka Curriculum, and the demand for higher creativity from teachers. This research contributes to the development of more holistic and meaningful Qur'anic learning methods in line with the Merdeka Curriculum. The study also emphasizes the challenge of balancing innovation in pedagogy with teacher readiness and curriculum alignment, which are critical for the successful integration of new learning methods.